AVALIAÇÃO DO EFEITO DO LASER DE BAIXA INTENSIDADE NO PROCESSO DE REPARO DE ALVÉOLOS PÓS-EXODONTIA TRATADOS COM HIDROXIAPATITA E OSSO BOVINO INORGÂNICO EM RATOS - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2016)
Biomaterials and the photobioengineering are techniques that emerged in order to enhance bone healing and prevent the reabsorption of sockets after the tooth extraction. The aim of this study was to evaluate the effect of low level laser therapy (LLLT) comparatively to the process of bone healing in post extraction sockets of rats treated with hydroxyapatite + β-tricalcium phosphate (HA) and inorganic bovine bone (IBB). Forty-eight male rats were divided into 6 groups and subdivided according to sacrifice time (7 and 14 days): C: clot, CL: Clot + LLLT, IBB: inorganic bovine bone, IBBL: inorganic bovine bone + LLLT, HA: hydroxyapatite + β-tricalcium phosphate and HAL: hydroxyapatite + β-tricalcium phosphate + LLLT. The LLLT (GaAlAs, λ780nm, 10mW, Ø0,4cm, 75J/cm2, 300s) was applied to the socket immediately after the extraction, the next day, in the third and fifth day. At 7 and 14 day, 4 animals per group were sacrificed. Samples were processed and stained with H-E for histological and histomorphometric analysis. At 7 day, greater presence of blood vessels was observed in all irradiated groups; as well as more quantity of osteoblasts but there was only statistically different between CL7 (clot + LLLT) and OB7 (inorganic bovine bone) groups. At 14 day, more blood vessels were counted in the irradiated groups; a greater presence of matrix bone was observed suggesting bone formation; however, without statistical difference. In the protocol used in this work, we conclude that LLLT had a tendency in the bioestimulation of the bone healing in its early phase based in the better proliferation of endothelial and osteoblastic cells.
Keywords: Alvéolo dental; Regeneração óssea; Substitutos ósseos; Terapia laser de baixa Intensidade; Dental socket; Bone regeneration; Bone substitutes; Low Intensity Laser Therapy; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA